(untitled) (American Journal of Islam and Society, 1991)
Introduction Anyone who reads the Qur’an carefully and endeavors to attain a proper understanding of its attitude towads science will face a great number of iiyiit which cover science in all its aspects. These fall into four categories: 1) matters related to the reality, horizons, and aims of science or, to put it more precisely, the “philosophy of science and theory of knowledge,” 2) the methodology of discovering scientific facts, 3) the laws that apply in the various fields of science-particularly natural sciences -called the pure sciences, and 4) those laws discovered through experimental methodology and meant to be applied by a person in hidher capacity as vicegerent of Allah (SWT) on earth, who has been entrusted with the task of creating a higher and better life and a finer world. This field is known as the applied sciences. There is undoubtedly a very close relationship between each of these categories. Philosophy analyzes the aims of science while methodology provides a modus operdndi for discovering facts; that is, it explains the laws and systems which control the cosmos, the world and life, and which protect their movements in time. In turn, these laws and systems furnish humanity with the formulae which enable individuals to explore the wondrous structureof creation. Consequently, these laws and systems become the means by which humanity can achieve the progress and development of human civilization. Such knowledge can free humanity from the drudgery of day-to-day earthly existence, raise its eyes to the heavens and satisfy those spiritual needs which distinguish it from all other creatures. An individual can thus perform more of the duties required of him/her in hidher capacity as vicegerent, and fulfill hidher role of bringing civilization and development to the world ...